Problems and Challenges of Cassava Plantation in KENETHAO District, Xayabouly Province - THYKEO, Phonesavanh; YANGSENXAY, Chahue; NOUANTHASING, Kommaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The objective was to study the problems and challenges of cassava growers in Kenethao district, Xayabouly province. This study was qualitative research. It is done by studying and analyzing data from documentary research through in-depth interviews as tool. Purposive sampling was used and data were collected with in-depth interviews. The target groups were village headman, growers, purchasers and from office of agriculture staffs. The results shown that the main problems and challenges firstly, cost generation is the main concerns of growers, due to low negotiation power of growers and the middle man on pricing of cassava, their experienced in cultivating cassava based on basic knowledge. While, the land is an importance factor that the growers must take in considerations to solve the problems of nutrient deficiency, soaking and increase the nutrients in cassava types. Following concerns are the insects and disease of cassava is one factor that decreases cassava production and quality. In summary, the tendency of cassava cultivation in the future will decline; the growers might change to plant others commercial crops instead depend on market.